PENGEMBANGAN BUKU BAHASA MADURA SEBAGAI PENUNJANG PEMBELAJARAN MUATAN LOKAL DI SEKOLAH DASAR - Riska Fita Lestari; Lutfi Irawan Rahmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2021)
The development of language science has an important role in using books as a medium of learning. Madura language is a local content subject that is introduced to students in elementary schools. The development of language science has an important role in using books as a medium of learning. Based on that background, the problem formulation in this study is how pepak development. This research uses Research and Development (R&D) approach. The subjects of the study were teachers and a Team of Experts consisting of Expert Lecturers and Madurese Culturalists. The data collection techniques in this study use observations, library studies, documentation, interviews, and questionnaires for prototype assessment. Data analysis techniques use qualitative descriptive. The result of this study is a product in the form of a prototype book in Madura language that will make it easier for elementary school students to learn it.